Dynamic Competitiveness of Indonesian Commodities in Major Export Destination - Hertiana Ikasari (Universitas Negeri Malang, 2024)
This study aims to analyze the export competitiveness and market position of the agricultural, manufacturing, and mining sectors in 10 main export destination countries (China, the United States, Japan, India, Singapore, Malaysia, South Korea, Thailand, the Netherlands, and the Philippines). This study uses secondary data sourced from UN COMTRADE for the period of 2013 – 2018. The data is categorized using a 2-digit Harmonized System (HS) classification. This study uses Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) analysis tools. The RCA estimation results show the export competitiveness of Indonesia’s agricultural, industrial, and mining products is still weak and strong in several major export destination countries. Meanwhile, the EPD estimation shows the Indonesia’s exports of agricultural, industry, and mining commodities mostly got rising star positions in some countries but losing opportunity positions in some other countries. The following suggestions proposed are based on the research. In general, the implications of policy to improve the competitiveness of export products in the manufacturing, agriculture, and mining industries are infrastructure improvement, expansion of the export market, improvement in the quality of human resources, and employment, increasing access to finance, increasing the quality and quantity of production in processing, agriculture and mining industries, and maintaining political